A simple inexpensive method for estimating underwater weight. - Thomas, T. R. (1978)
A description is given of a simple, inexpensive and versatile method for estimating underwater weight. The use of a portable stock tank allows the determination of % Fat by underwater weighing without requiring a swimming pool, built-in tank, or special facility. Twenty-eight college students were weighed on two separate testing sessions 24-48 hours apart. Ten trials were performed at each session. The mean of the last five trials was used in determining underwater weight. The test-retest reliability coefficient was high, r = 0.98, and most of the successive trial correlations were above 0.99. The mean % Fat for the women (N = 9) was 22.2 +/- 5.9 and for the men (N = 19) was 13.7 +/- 5.1.